Interpreting kick dynamics in professional rugby union utilising clustering analysis - Scott, G.; Bezodis, N. E.; Bennett, M.; Waldron, M.; Church, S.; Kilduff, L. P.; Brown, M. R. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Previous studies have identified the importance of kicking in modern rugby union, irrespective of league, level, or player gender (1,2). However, there is limited research that quantifies the physical requirements of supporting players during kicking. This study aimed to interpret the spatio-temporal requirements of kick collection when considering (i) different kick types, (ii) kick outcomes, and (iii) playing circumstances. A secondary aim was to investigate whether kicks can be grouped on these metrics, with potential to influence future kicking and training strategies. METHODS: Coded video analysis files were downloaded from 144 matches within the 2021-22 season of the United Rugby Championship. All kicks from hand were collated and 4451 kicks were analysed after data cleansing. Distance and time from the location and instant of the kick to the collection were determined and used to calculate the average speed. Descriptive statistics on these metrics were reported for kick types (n = 7) and kicks in different zones (n = 5). This was repeated for kicks grouped by the outcome of the kick itself, such as whether the kick was collected on the full or on the bounce, and kicks grouped by the action of the collecting player, such as whether the ball was passed or kicked immediately by the collecting player. K-means clustering was utilised to group kicks based on their distance and collection time. RESULTS: Mean kick distance by type ranged from 22.7 to 51.4 m, with corresponding collection times ranging from 2.9 to 4.4 s. Mean kick distance for different zones of the field and collection times ranged from 19.8 to 44.0 m and 2.4 to 4.2 s, respectively. Distances and collection times also varied between different kicking outcomes and field circumstances. The cluster analysis indicated four distinct groups, where cluster centres were located at the coordinates (25.7 m, 4.2 s), (57.5 m, 6.2 s), (20.8 m, 2.3 s), and (48.9 m, 3.7 s), respectively. CONCLUSION: The differences in mean spatiotemporal values highlighted a difference between long `territorial` kicks and shorter `contestable` kicks. Outcomes tended to match this, with balls caught by the opposition being longer distanced on average, compared to those caught by the kicking team. Two of the four identified clusters represented longer-distance kicks: one with a higher mean collection time and one with a lower mean collection time. The other two comprised shorter-distance kicks, again with each cluster differing by a higher or lower mean collection time. This suggests that kicks can be broadly split into four key groups, fast and slow territorial kicks as well as fast and slow contestable kicks. These groups can be utilised to create drills and tactics for different in-match scenarios and also to inform the demands for return-to-play protocols.